Trends in Hospitalizations and Survival of Acute Decompensated Heart Failure in Four US Communities (2005–2014): ARIC Study Community Surveillance. Issue 1 (3rd July 2018) - Chang, Patricia P.; Wruck, Lisa M.; Shahar, Eyal; Rossi, Joseph S.; Loehr, Laura R.; Russell, Stuart D.; Agarwal, Sunil K.; Konety, Suma H.; Rodriguez, Carlos J.; Rosamond, Wayne D.
Abstract : Background: Community trends of acute decompensated heart failure (ADHF) in diverse populations may differ by race and sex. Methods: The ARIC study (Atherosclerosis Risk in Communities) sampled heart failure-related hospitalizations (≥55 years of age) in 4 US communities from 2005 to 2014 using International Classification of Diseases, Ninth Revision, Clinical Modification codes. ADHF hospitalizations were validated by standardized physician review and computer algorithm, yielding 40 173 events after accounting for sampling design (unweighted n=8746). Results: Of the ADHF hospitalizations, 50% had reduced ejection fraction, and 39% had preserved EF (HFpEF). HF with reduced ejection fraction was more common in black men and white men, whereas HFpEF was most common in white women. Average age-adjusted rates of ADHF were highest in blacks (38.1 per 1000 black men, 30.5 per 1000 black women), with rates differing by HF type and sex. ADHF rates increased over the 10 years (average annual percentage change: black women +4.3%, black men +3.7%, white women +1.9%, white men +2.6%), mostly reflecting more acute HFpEF. Age-adjusted 28-day and 1-year case fatality proportions were ≈10% and 30%, respectively, similar across race-sex groups and HF types. Only blacks showed decreased 1-year mortality over time (average annual percentage change: black women –5.4%, black men –4.6%), with rates differing by HF type (average annual percentage change: black women HFpEF –7.1%, black men HF with reduced ejection fraction –4.7%). Conclusions: Between 2005 and 2014, trends in ADHF hospitalizations increased in 4 US communities, primarily driven by acute HFpEF. Survival at 1 year was poor regardless of EF but improved over time for black women and black men. Abstract : Supplemental Digital Content is available in the text.